Epidemiology of human leptospirosis in urban and rural areas of Brazil, 2000–2015 - Galan, Deise I.; Roess, Amira A.; Pereira, Simone Valéria Costa; Schneider, Maria Cristina (PloS one, 2021)
Leptospirosis is one of the most widespread zoonosis in the world and Brazil has the highest number of cases in Latin America. Transmission occurs mainly through exposure to water and soil contaminated by the urine of infected animals. The goals of this study are to describe the geographic distribution, demographic characteristics and exposure factors of urban and rural cases of leptospirosis, and identify spatial clusters in urban and rural areas of Brazil. A retrospective epidemiological study was carried out using 16 years (2000-2015) of surveillance data from the Brazilian Ministry of Health. Cases were described by age, sex and race, and exposure factors were characterized in urban and rural areas. A spatial autocorrelation analysis was conducted using local Moran's I to identify urban and rural clusters of disease. On average 3,810 leptospirosis cases were reported annually with higher numbers in urban areas. National urban and rural incidence rates were the same (1.9 cases/100,000 population), however, regional differences were observed. Urban incidence rates were higher in the North and Northeast regions, while rural incidence rates were higher in the Southeast and South. The main exposure factor reported in urban and rural areas was exposure to places with signs of rodents, followed by flood in urban areas and agriculture and animal farming in rural areas. Clusters of leptospirosis were identified in densely populated urban areas of the North, Southeast and South regions, while rural clusters were concentrated in of the Southern region with large agriculture and animal farming practices. This study highlights that leptospirosis is an important public health problem in both urban and rural areas of Brazil. The results provide decision-makers with detailed information about where disease incidence is high and can be used in the development of prevention and control strategies for priority areas and risk groups.